2023
DOI: 10.1186/s41687-023-00616-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 and effects of booster vaccination with BNT162b2 on six-month long COVID symptoms, quality of life, work productivity and activity impairment during Omicron

Abstract: Background Longitudinal estimates of long COVID burden during Omicron remain limited. This study characterized long-term impacts of COVID-19 and booster vaccination on symptoms, Health-Related Quality of Life (HRQoL), and Work Productivity Activity Impairment (WPAI). Methods Outpatients with ≥ 1 self-reported symptom and positive SARS-CoV-2 test at CVS Health United States test sites were recruited between 01/31 and 04/30/2022. Symptoms, EQ-5D and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 26 publications
7
22
0
Order By: Relevance
“…While side-by-side comparisons with other studies are impaired by design and methodological differences, our results are generally in line with prior work on long COVID. Our observed prevalence rates of long COVID are in line with published estimates among non-hospitalized US patients [ 2 , 3 , 4 , 5 , 6 , 7 , 15 , 25 , 26 ]. Four weeks after the initial infection, approximately 30% of study participants reported experiencing at least three symptoms consistent with long COVID, and 40% reported experiencing at least two symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…While side-by-side comparisons with other studies are impaired by design and methodological differences, our results are generally in line with prior work on long COVID. Our observed prevalence rates of long COVID are in line with published estimates among non-hospitalized US patients [ 2 , 3 , 4 , 5 , 6 , 7 , 15 , 25 , 26 ]. Four weeks after the initial infection, approximately 30% of study participants reported experiencing at least three symptoms consistent with long COVID, and 40% reported experiencing at least two symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…The observed differences in long COVID symptoms outcomes by vaccination status support other investigations suggesting that vaccination is associated with reduced risk for long COVID [2][3][4][5][6][7]15,26]. In this study, we found that six months after the initial infection, the bivalent cohort had approximately a 40% lower risk of long COVID, defined as either the presence of at least two or three symptoms.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In a study comparing ChAdOx with mRNA vaccines, an inability to work was reported most frequently after a first dose of ChAdOx (33.6% over days 1–2; 10% over ≥3 days) and a second dose of mRNA-1273 (29.6% over days 1–2; 9.2% over ≥3 days) [ 35 ]. Although COVID-19 and long COVID have a greater impact on local and systemic events and work productivity than vaccines [ 45 , 46 ], a vaccine of limited reactogenicity is critical for reducing the impact on work and daily activities.…”
Section: Discussionmentioning
confidence: 99%